Synthesis and characterization of a mesoporous and three dimensional N-doped graphene structure via the Couette-Taylor flow and hydrothermal method. Issue 12 (September 2017) - Kang, Bong Kyun; Song, Young Hyun; Park, Won Kyu; Kwag, Sung Hoon; Lim, Byeong Seok; Kwon, Seok Bin; Yang, Woo Seok; Yoon, Dae Ho
Abstract: In this study, graphite oxide was successfully synthesized from bulk graphite flakes using a Couette-Taylor flow reactor. A high yield (∼93%) of single-layer and few-layer graphene oxide sheets was achieved in this study within a reaction time of one hour by optimizing the conditions. The graphite oxide was effectively exfoliated using the Taylor vortex flow with shearing stress. The degree of oxidation and the graphite oxide morphology were then studied. In addition, mesoporous and three-dimensional nitrogen-doped graphene structures were prepared via graphene oxide sheets and facile solution phase synthesis followed by thermal treatment. The nitrogen in the pyrrolidone ring of PVP was decomposed and incorporated into the carbon network, including pyridinic-N and graphitic-N. Furthermore, the mesoporous and three-dimensional Ni1.5 Co1.5 [Co(CN)6 ]2 Prussian blue analogue (PBA) and NiCo sulfides/N-doped graphene hybrid composite structures were successfully demonstrated via facile hydrothermal method.